2021
DOI: 10.1038/s41419-021-04447-4
|View full text |Cite
|
Sign up to set email alerts
|

RPRD1A stabilizes NRF2 and aggravates HCC progression through competing with p62 for TRIM21 binding

Abstract: NRF2 is the master transcriptional activator of cytoprotective genes and Kelch-like ECH-associated protein 1 (Keap1), a biosensor for electrophiles and oxidation, promotes NRF2 degradation in unstressed conditions. SQSTM1/p62, an oncogenic protein aberrantly accumulated in hepatocellular carcinoma (HCC), binds and sequestrates Keap1, leading to the prevention of NRF2 degradation. Here, we show that p15INK4b-related sequence/regulation of nuclear pre-mRNA domain-containing protein 1A (RPRD1A) is highly expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…TRIM21 directly interacts with and ubiquitinates p62 at the K7 residue to abolish Keap1 sequestration, downregulating the Nrf2 redox pathway to induce cell death in response to oxidative stress (130). In line with this, TRIM21-deficient heart tissues and cells enhance p62mediated sequestration of Keap1 to protect themselves from doxorubicin-induced ferroptosis (130)(131)(132). Phosphatase and tensin homologue (PTEN), a tumor suppressor protein that regulates Nrf2 expression in a Keap1-independent manner (133), can be upregulated by nuclear Prothymosin-a (PTMA) at the transcriptional level.…”
Section: Role Of Trim21 In Cancer Treatmentmentioning
confidence: 91%
“…TRIM21 directly interacts with and ubiquitinates p62 at the K7 residue to abolish Keap1 sequestration, downregulating the Nrf2 redox pathway to induce cell death in response to oxidative stress (130). In line with this, TRIM21-deficient heart tissues and cells enhance p62mediated sequestration of Keap1 to protect themselves from doxorubicin-induced ferroptosis (130)(131)(132). Phosphatase and tensin homologue (PTEN), a tumor suppressor protein that regulates Nrf2 expression in a Keap1-independent manner (133), can be upregulated by nuclear Prothymosin-a (PTMA) at the transcriptional level.…”
Section: Role Of Trim21 In Cancer Treatmentmentioning
confidence: 91%
“…Transcriptional changes, e.g., the loss of RBM47, are associated with KEAP1 mRNA stabilization, and the existence of alternatively spliced NRF2 variants also contributes to NRF2 augmentation [7,8]. Furthermore, sequestration of KEAP1 by NRF2competitive-binding proteins including TRIM21, RPRD1A, and FAM129B was found in NRF2-addicted cancer models [9][10][11]. Thus, it remains to explore the best way to define the NSCLC with high NRF2 addition.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…TRIM21 was highly expressed in HCC, and TRIM21 genetic ablation protected the liver from oxidative injury and reduced the occurrence of HCC by suppressing the p62-Kelch-like ECH-associated protein 1 (Keap1)-NF-E2-related factor 2 (Nrf2) pathway . Another study reported that p15INK4b-related sequence/regulation of nuclear pre-mRNA domaincontaining protein 1A (RPRD1A) interacted with TRIM21 by increasing the aggregation of p62 and Keap1 to promote nuclear translocation of Nrf2, which further contributes to the progression of HCC (Feng et al, 2021). However, the down-regulation of TRIM21 was associated with a poor prognosis in patients with HCC (Ding et al, 2015).…”
Section: An Overview Of the Tripartite Motifs Protein Familymentioning
confidence: 99%